Legal Politics of Spatial Utilization for Residential Areas in the Regional Spatial Plan Regulation of Bima City (2021-2024) - M. Mustamin; Taufik Firmanto (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2026)
This study aims to examine the extent to which the regulation of residential areas and the enforcement of spatial utilization laws are implemented under the Bima City Regional Spatial Plan (RTRW) for the period 2021–2024, to identify obstacles in its implementation, and to formulate more effective spatial planning policy recommendations. The main issue addressed in this research concerns the inconsistency between actual land use and the spatial designation stipulated in the RTRW, as well as the weak enforcement of spatial planning regulations in residential areas. This study employs a qualitative approach with a descriptive-analytical design. Data sources consist of primary legal materials in the form of regional regulations governing the Bima City RTRW and other related legislation, as well as secondary legal materials derived from scholarly literature and relevant policy documents. Data were analyzed using qualitative methods through normative interpretation of legal provisions and their implementation in practice. Although regulatory frameworks exist, enforcement of residential spatial utilization remains ineffective. The main obstacles identified include weak supervisory mechanisms, limited institutional capacity, low public awareness and understanding of spatial planning regulations, and the influence of political factors in the law enforcement process. This study recommends enhancing public dissemination of the RTRW, strengthening the capacity and coordination of law enforcement authorities, and applying firm and consistent sanctions for spatial planning violations. It underscores the importance of strengthening spatial planning legal politics to balance residential development and sustainable urban management in Bima City.